Teachers’ opinions about elitism in gifted education - Branka Radulović (South African Journal of Education)
Although teachers’ attitudes towards gifted students and gifted education have been monitored more intensively since the 1990s, we still do not have a clear and definitive picture. Therefore, with the research reported on here we examined teachers’ opinions about the connection between gifted education and elitism and how they viewed the need for grouping gifted students. The sample consisted of 432 primary and secondary school teachers. The main results show teachers’ neutral opinions towards the grouping of gifted students and the correlation to elitism. Significant differences were obtained in the teachers’ opinions for demographic characteristics, i.e. the school type (primary or secondary) and the school location (urban or rural). The results are in line with the general idea that education should be accessible to everyone according to their abilities in order to overcome equating gifted education with the rich elite.